CRITICAL FACTORS IN MANAGING CUSTOMERSUPPLIER RELATIONS - Aparna Pasi, Satya Jaya (European Scientific Journal, ESJ, 2014)
This paper approaches the customer-supplier relations in tailored offshore software development projects. The objective of the study is to evaluate the critical factors that can accomplish the project lead’s task to manage the project well. The root cause of software project failures is due to the problems in customer-supplier relations. An analysis of the literature suggests that the managing customer- supplier relations in tailored offshore software development have been relatively unexplored. Therefore, a detailed investigation of the critical factors in managing customer-supplier relations in offshore software development is presented. In this study we collected qualitative data through theme-based open-ended interviews, and analyzed it through a grounded theory approach. Our analysis shows symmetrical power relations, unrealistic promises in contract negotiations, expectation management, transparency and honesty, communication as factors in managing customersupplier relations. We claim that these factors can be considered critical in managing offshore software development projects effectively.